A reputation-based model for mobile agent migration for information search and retrieval. Issue 5 (October 2017) - Zuo, Yanjun; Liu, Jigang
Highlights: A reputation-based model is developed for mobile agent migration to search and retrieve information in decentralized, open systems. We use opinion-based belief structure to represent, aggregate and finally calculate the reputation of an information host. The proposed approach allows users to rank each information host's quality of service based on a set of evaluation categories. Then, a comprehensive, final reputation of the host is obtained by aggregating those specific category reputations. The transferable belief model is used to represent and rank the category reputation. We have conducted an experiment using the Aglets technology to illustrate mobile agent migration. Abstract: Mobile agent technology has been used in various applications including e-commerce, information processing, distributed network management, and database access. Information search and retrieval can be conducted by mobile agents in a decentralized system. As compared with the client/server model, the mobile agent approach has an advantage of saving network bandwidth and offering flexibility in information search and retrieval. In this paper, we present a model for mobile agents to select the most reputable information host to search and retrieve information. We use opinion-based belief structure to represent, aggregate and calculate the reputation of an information host. Since reputation is a multi-faced concept, our approach first allows the users to rank each information host's quality of service based on a set of evaluation categories. Then, a comprehensive, final reputation of the host is obtained by aggregating those specific category reputations. To recognize the subjective nature of a reputation, the transferable belief model is used to represent and rank the category reputation. Experiments are conducted using the Aglets technology to illustrate mobile agent migration.